Strategic Governance for Sustainable Development in the Defense Industry - Sarjito, Aris (West Science Interdisciplinary Studies, 2024)
The defense industry, crucial for national security, is increasingly pressured to integrate sustainability into its governance practices. This research aims to develop a strategic governance framework that effectively incorporates sustainability principles into the defense sector. Utilizing qualitative research methods and secondary data, including government reports, industry publications, and academic studies, the study analyzes existing governance practices, identifies key challenges, and proposes actionable strategies. Findings reveal that while the defense industry has implemented some sustainability measures, such as Environmental Management Systems and sustainable procurement policies, these efforts are often inconsistent and hindered by regulatory constraints, financial limitations, cultural resistance, and technological barriers. A proposed strategic governance framework includes clear sustainability goals, regulatory reforms, enhanced transparency, and leveraging technological innovation. The study concludes that a comprehensive approach, integrating policy recommendations, best practices, and targeted implementation strategies, is essential for embedding sustainability into defense governance. This framework can guide the defense industry in balancing security needs with environmental and social responsibilities, promoting long-term sustainable development. Keywords: defense industry, environmental management systems, strategic governance, sustainable development